Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3